Laminated composites of continuous steered fibres along curved paths: characterisation and optimisation - Hassan, Ali Jameel (2020)
The need for lighter structure in the airplane industry has led to wide applications of fibre-reinforced composites due to their higher specific strength and specific stiffness. The directionality of these materials has motivated the researchers to take advantage of this feature. An investigation has been performed in this thesis by using the optimisation process to enhance structural performance or minimize structural weight. It is possible to reduce stresses in the most concentrated regions in the composite structures, such as notches and holes, by steering the fibre paths in a curved manner. In general, steering the fibre can lead to a good-balanced distribution of the local fibre angles in the composite materials. The directional properties in the laminated structures can be designed. An optimisation framework has been developed and applied to find the optimal design variables for the optimisation design as present in this thesis. A genetic algorithm in a Matlab was used for its robustness to find the global minimum point and an excellent ability to work in a noisy environment of the objective function. In this framework, a technique of the client and server has been employed to facilitate the communications between the Matlab as the optimiser and Abaqus/Standard as stress analysis solver. Efforts have been made to avoid time delay during opening the startup session dialogue box when Abaqus/CAE is called for each iteration of the optimisation. Optimisation of different orders of variations of the local fibre angles has been investigated concerning their effects on the local stiffness, as the ability to resist buckling load. The first-order variation has approved to be the most significant, especially when the variation was perpendicular to the direction of the applied load. A gap of variable width is present between curved fibre tow paths. It leads to a non-uniform distribution of fibre volume fraction. Therefore, the stiffness and buckling response have been influenced negatively. A laminated composite cylinder can be designed using steered fibre. Therefore, the influence of steered fibre has been investigated in terms of the structural performance of circular and elliptical cylindrical shells. The local fibre angles vary linearly around the circumference. Optimum local fibre angles have been obtained, that result in a maximum buckling capacity. Steering the fibre around the elliptical cylindrical shells improves the structural performance by redistributing loads from the flatter areas to the higher curved areas. The influence of the aspect ratio of the elliptical shells on the enhancement of the ability of the structure to resist the buckling load has been studied. The directions of the applied bending moment for both circular and elliptical cylindrical shells have been investigated, to find the applicable range that offers an improvement in buckling load. The maximum stress criterion and Tsai-Wu criterion have been used to predict the failure load of curved fibre laminates. The gaps of variable width led to reduced strength with an exception for some patterns of curvilinear fibre panels, where no significant difference in failure loads has been found between the laminates of the uniform and non-uniform fibre volume fraction distributions. A mesoscale modelling of the curvilinear tow with its variable gap width has been established to determine the constitutive relationship of the material. The effective material properties for different configurations of local fibre angles have been predicted using a unit cell model based on translational symmetries. The periodic boundary conditions have been derived. The analysis has been carried out using the Python script, which is considered as a secondary development of Abaqus/CAE. Extensive verifications have been conducted. A good corresponding has been achieved between UC models and rule of mixtures (ROM) for the obtained effective material properties.